The Economic Policy of Japanese Naval Government in South Sulawesi in the Second World War 1942 -1945 - Rasyid Asba (Diponegoro University, 2017)
The Japanese economic policy in South Sulawesi seemed to have different policies when compared to the other colonies in Indonesia. It was indicated by leadership typology of Japanese Navy which based in Makassar, Bukittinggi, and Java. In South Sulawesi, the policy was more focused on the compliance of logistic materials by strengthening on clothing industry, plantation of cotton and castor oil, and fisheries. The important policy of the army was the agricultural massive production sector to support the war. In addition, the agricultural and industrial sectors were also developed such as salt, castor oil, textile, silk, handicrafts and the like. Those phenomena analyzed by historical method. It used archives such as Japanese occupation reports in Makassar, Romusha archives in Makassar, and Japanese local politic documents in South Sulawesi. The reports on Japanese economic activities in South Sulawesi were also consulted. Information from magazines and newspapers were also taken such as Pemberitaan Makassar, Bintang Timoer, Sinar Baroe, Soeara Asia, Hong Po, and Pemandangan. In addition to, it has complied oral history with direct interviews to the people who are still alive and experienced on the era. The Japanese economic policies in South Sulawesi influenced great changes in new economic structure on the emergence of the diversification of popular-based commodity especially clothing and foodstuff during the war. That was the reason why people in South Sulawesi directed to execute intensification of agriculture in a professional productive manner supported by communal industrial policy.